Formation of Aluminum Titanate with Small Additions of MgO and SiO2 - Guedes-Silva,Cecilia Chaves (2016)
The formation of aluminum titanate was investigated by isothermal treatments of samples obtained from equimolar mixtures of alumina and titania, containing small amounts of silica and magnesia. Results of differential thermal analysis and Rietveld refinements of data collected by X-ray powder diffraction (XRPD) showed that additions of silica in amounts used in this work did not influence the formation of aluminum titanate. However, the presence of magnesia favored the formation of aluminum titanate in two steps, first one by incorporating Mg2+ into Al2TiO5 lattice during its initial formation, and the second one by accelerating the Al2TiO5 formation, contributing to large quantities of this phase. MgO doped samples have also developed a more suitable microstructure for stabilizing of Al2TiO5, what make them promising for applications such as thermal barriers, internal combustion engines and support material for catalyst.